Increased Mast Cell Counts in Benign and Malignant Salivary Gland Tumors - Zohreh Jaafari-Ashkavandi; Mohammad-Javad Ashraf (Tabriz University of Medical Sciences, 2014)
Background and aims. Mast cells are one of the characteristic factors in angiogenesis, growth, and metastatic spread of tumors. The distribution and significance of mast cells in many tumors have been demonstrated. However, few studies have evaluated mast cell infiltration in salivary gland tumors. In this study, mast cell counts were evaluated in benign and malignant salivary gland tumors. Materials and methods. This descriptive and cross-sectional study assessed 30 cases of pleomorphic adenoma, 13 cases of adenoid cystic carcinoma, 7 cases of mucoepidermoid carcinoma (diagnosed on the basis of 2005 WHO classification), with adequate stroma in peritumoral and intratumoral areas, and 10 cases of normal salivary glands. The samples were stained with 5% diluted Giemsa solution and the average stained cell counts were calculated in 10 random microscopic fields in peri- and intra-tumoral areas. Data were analyzed by t-test and Mann-Whitney and Krusskal-Wallis tests. Results. The average mast cell counts increased in the tumors compared to normal salivary glands. There was no significant difference between benign and malignant tumors and also between different malignant tumors. Infiltration was significantly denser in peri-tumoral stroma in both tumoral groups (P = 0.001). Minor salivary glands contained significantly more numerous mast cells. Conclusion. Although mast cell counts increased in benign and malignant salivary gland tumors, there were no significant differences between the tumoral groups. Further studies are suggested to determine the type of these cells which might be useful in the assessment of biological nature of the tumor and its future treatment modality